Association between shammah use with periodontal disease and shammah-induced leukoplakia-like lesion among adult males in dawn valley, Yemen - Saeed Al-Tayar, Badr Abdullah (2015)

(untitled)
Background: The traditional type of smokeless tobacco (SLT) used in the Arabian Peninsula, especially common in Yemen is called shammah. Shammah and other risk factors play an important role in development of oral diseases. Objectives: The present study has been undertaken to determine the prevalence of shammah use and to determine the association between shammah use with periodontal disease and oral leukoplakia-like lesions. Other associated factors with periodontal disease as well as with oral leukoplakia-like lesions were also determined. Materials and Methods: A cross sectional study was conducted on 346 randomly selected adult males. Multistage random sampling was used to select the study location. After completing the structured questionnaire interviews, all the participants underwent clinical exanimation for periodontal health status and oral leukoplakia-like lesions. Periodontal status was recorded using the Community Periodontal Index (CPI). Clinical features of oral leukoplakia- like lesions were characterized based on the grades of Axéll et al. (1976). Chi-square test was used for assessing significant differences in shammah status in respect to periodontal disease and oral leukoplakialike lesions. Univariable logistic regression and multivariable logistic regression were selected for assessing potential associated factors. Results: Out of 346 male participants aged 18 years and older, 68 reported being current shammah users. The prevalence of current shammah use was 19.7% (95% CI: 15.6%, 24.2%). Chi-square test detected that significant differences exists between the study groups (i.e., never, former, and current shammah users) in respect to the presence of periodontal disease (P= 0.001) as well as to the presence of oral leukoplakia-like lesion (P=0.001). Multivariable logistic regression analysis revealed that age, family income, former shammah user, current shammah user, and annual duration of shammah use were statistically associated with the presence of periodontal disease [Adjusted odds ratio (AOR)= 1.05; 95% CI: 1.03, 1.07; P= 0.001], (AOR= 2.01; 95% CI: 1.16, 3.47; P= 0.012), (AOR= 2.92; 95% CI: 1.20, 7.10; P= 0.018), (AOR= 7.25; 95% CI: 3.84, 13.70; P= 0.001), and (AOR= 2.19; 95% CI: 1.47, 3.24; P= 0.001), respectively. The multivariable analysis also revealed that age, no formal or primary level of education, former shammah user, current shammah user, and frequency of shammah use per day were statistically associated with the presence of oral leukoplakia-like lesion ( AOR= 1.03; 95% CI: 1.01, 1.06; P= 0.006), (AOR= 8.65; 95% CI: 2.81, 26.57; P= 0.001), (AOR= 3.65; 95% CI: 1.40, 9.50; P= 0.008), (AOR= 12.99; 95% CI: 6.34, 26.59; P= 0.001), and (AOR= 1.17; 95% CI: 1.02, 1.36; P= 0.026), respectively. Conclusion: The results revealed that periodontal disease and oral leukoplakia-like lesions were significantly associated with shammah use. Therefore, it is important to develop comprehensive shammah prevention programmes in Yemen.